Michael without apology : a novel - Hyde, Catherine Ryan (Lake Union Publishing, 2025)
Michael Woodbine was seven years old when a near-fatal fireworks accident scarred him and led to his placement in foster care. Now a college freshman, he is still trying to hide the effects of his trauma from his classmates, his adoptive family, and himself. When Michael signs up for a film class, he meets Robert Dunning, a teacher who wears his own scars unapologetically. Robert encourages Michael to make a documentary that explores body image and self-perception. Michael places an ad seeking people who feel unattractive and rejected by society-and is surprised to learn that this is essentially everyone. Although some participants are recovering from injuries or surgeries, others are dealing with more everyday factors like aging or the changes to a body from giving birth. As he collects these stories-and finally tells his own-Michael feels more connected to the world than he ever has before. But he knows his journey of self-acceptance has one more obstacle: his crushing doubts about why his birth parents wouldn't fight to keep him.